2013
DOI: 10.1016/j.jvs.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of ruptured infrarenal abdominal aortic aneurysm is associated with lower 30-day mortality and better 5-year survival rates than open surgical repair

Abstract: For r-AAA, EVAR reduces the 30-day mortality and improves long-term survival up to 5 years. However, whereas open survivors require few graft-related interventions, up to 23% of EVAR patients will require reintervention for endoleaks or graft migration. Close follow-up of all EVAR survivors is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 32 publications
4
78
0
4
Order By: Relevance
“…EVAR has expanded access to repair because ruptures may have been prevented, particularly for oldest patients, and life expectancy may have been prolonged meaningfully (3). These patients in previous studies were older men and had higher rates of hypertension and COPD; they were more likely to undergo elective EVAR rather than emergent EVAR and were comparable with the patients in our present report (7,8,12). A history of hypertension strongly predicted survival of EVAR (8,13).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…EVAR has expanded access to repair because ruptures may have been prevented, particularly for oldest patients, and life expectancy may have been prolonged meaningfully (3). These patients in previous studies were older men and had higher rates of hypertension and COPD; they were more likely to undergo elective EVAR rather than emergent EVAR and were comparable with the patients in our present report (7,8,12). A history of hypertension strongly predicted survival of EVAR (8,13).…”
Section: Discussionsupporting
confidence: 84%
“…Our current practice indicates that many patients with a clinical diagnosis of a rupture are transferred from smaller hospitals and are increasingly managed in vascular units. A previous report showed that 59% were transferred from an outside facility and 41% were direct admissions (8). In our study, 36% (9/25) of patients were transferred from local hospitals without surgical service to our hospital.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Compared with open repair, EVAR may offer significant survival benefits in elective surgery patients aged over 80 years (risk ratio 3.87, 95% CI 3.19-4.68) and a lower prevalence of complications [22,23]. A large randomised controlled trial (the IMPROVE trial) comparing EVAR and open repair for ruptured AAA is currently recruiting participants in the UK, and is due to report in 2014/15 [24].…”
Section: Emergency Abdominal Aortic Aneurysm Repairmentioning
confidence: 99%